Some Sum

Calculus Level 5

x = 1 y = 1 1 x 2 y + y 2 x = A ζ ( B ) \large \sum _{x=1}^{\infty }\sum _{y=1}^{\infty }\frac{1}{x^2y+y^2x}=A\zeta \left(B\right)

Find A + B A+B .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aareyan Manzoor
Jul 5, 2019

x = 1 y = 1 1 x y ( x + y ) = x = 1 y = 1 1 x y 0 e ( x + y ) t dt = 0 ( x = 1 e x t x ) ( y = 1 e y t y ) dt = 0 ln 2 ( 1 e t ) dt \sum_{x=1}^{\infty }\sum_{y=1}^{\infty }\frac{1}{xy(x+y)}= \sum_{x=1}^{\infty }\sum_{y=1}^{\infty }\frac{1}{xy} \int_0^\infty e^{-(x+y)t} \text{dt}= \int_0^\infty \left( \sum_{x=1}^{\infty } \dfrac{e^{-xt}}{x} \right)\left(\sum_{y=1}^\infty \dfrac{e^{-yt}}{y} \right) \text{dt} =\int_0^\infty \ln^2 \left( 1-e^{-t}\right) \text{dt} by making a change of variable with from t 1 e t t \to 1-e^{-t} , the integral is = 0 1 ln 2 ( t ) 1 t dt = n = 0 0 1 t n ln 2 ( t ) dt = n = 0 2 n 2 0 1 t n dt = n = 0 2 ( n + 1 ) 3 = 2 ζ ( 3 ) = \int_0^1 \dfrac{\ln^2 (t)}{1-t} \text{dt} = \sum_{n=0}^\infty \int_0^1 t^n \ln^2(t) \text{dt}=\sum_{n=0}^\infty \dfrac{\partial^2}{\partial n^2}\int_0^1 t^n \text{dt} =\sum_{n=0}^\infty \dfrac{2}{(n+1)^3} = \boxed{2\zeta(3)}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...